The Application of Art Therapy in Patients with Hallucinations: A Literature Review - Riza Arisanty Latifah; Yori Yolanda; Titin Indriati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Art Therapy is one of the non-pharmacological therapies in counseling which can be used to reduce anxiety and manage emotions such as stress, depression, and self-doubt. The forms of art therapy activities are very varied covering construction painting, collage, print making and drawing. To determine the application of art therapy in hallucination patients. This article uses a literature review searched through the Google Scholar and pubmed database, with the keywords Art therapy, Hallucinations, drawing and painting, which are limited from 2021-2025. The strategy used by the researchers in searching and selecting the articles is the PICO framework. For this study we searched and found the titles and abstracts of 286 pieces of literature on Google Scholar and pubmed. Then, the 8 core articles were selected based on the inclusion criteria of art therapy application hallucination patients with hallucination. The literature review provides evidence supporting the application of art therapy in hallucination patients.